A novel technology for home monitoring of lupus nephritis that tracks the pathogenic urine biomarker ALCAM - Lei, Rongwei; Vu, Binh; Kourentzi, Katerina; Soomro, Sanam; Danthanarayana, Adheesha N.; Brgoch, Jakoah; Nadimpalli, Suma; Petri, Michelle; Mohan, Chandra; Willson, Richard C. (Frontiers in Immunology, 2022)
The gold standard for diagnosis of active lupus nephritis (ALN), a kidney biopsy, is invasive with attendant morbidity and cannot be serially repeated. Urinary ALCAM has shown high diagnostic accuracy for renal pathology activity in ALN patients. Lateral flow assay (LFA) for assaying uALCAM were engineered using persistent luminescent nanoparticles, read by a smartphone. The stability and reproducibility of the assembled LFA strips and freeze-dried conjugated nanoparticles were verified, as was analyte specificity. The LFA tests for both un-normalized uALCAM (AUC=0.93) and urine normalizer (HVEM)-normalized uALCAM (AUC=0.91) exhibited excellent accuracies in distinguishing ALN from healthy controls. The accuracies for distinguishing ALN from all other lupus patients were 0.86 and 0.74, respectively. Periodic monitoring of uALCAM using this easy-to-use LFA test either by the patient at home could potentially accelerate early detection of renal involvement or disease flares in lupus patients, and hence reduce morbidity and mortality.